2017
DOI: 10.1093/mnras/stx363
|View full text |Cite
|
Sign up to set email alerts
|

X-ray spectroscopy of the z = 6.4 quasar SDSS J1148+5251

Abstract: We present the 78-ks Chandra observations of the z = 6.4 quasar SDSS J1148+5251. The source is clearly detected in the energy range 0.3-7 keV with 42 counts (with a significance 9σ). The X-ray spectrum is best-fitted by a power-law with photon index Γ = 1.9 absorbed by a gas column density of N H = 2.0We measure an intrinsic luminosity at 2-10 keV and 10-40 keV equal to ∼ 1.5 × 10 45 erg s −1 , comparable with luminous local and intermediate-redshift quasar properties. Moreover, the X-ray to optical power-law … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 103 publications
2
25
0
Order By: Relevance
“…The best-fit photon index is Γ = 1.59 +0.61 −0.57 with C-stat = 20.9 for 33 degrees of freedom. This value of Γ is consistent with the one found by Gallerani et al (2017;Γ = 1.6 +0.49 −0.49 ). SDSS J0100+2802 (z = 6.30).…”
Section: Analysis Of the Five Qsos With The Best Photon Statisticssupporting
confidence: 92%
See 1 more Smart Citation
“…The best-fit photon index is Γ = 1.59 +0.61 −0.57 with C-stat = 20.9 for 33 degrees of freedom. This value of Γ is consistent with the one found by Gallerani et al (2017;Γ = 1.6 +0.49 −0.49 ). SDSS J0100+2802 (z = 6.30).…”
Section: Analysis Of the Five Qsos With The Best Photon Statisticssupporting
confidence: 92%
“…), because of the smaller number of counts. This spectrum is characterized by a flatter power-law slope due to the presence of J1148+5251, that has a flatter photon index (see Gallerani et al 2017). However, this value is still consistent, within the errors, with those present in the literature.…”
Section: Mean X-ray Properties Of the Most Distant Quasarsmentioning
confidence: 99%
“…Assuming the Eddington luminosity for RD J1148+5253, the super massive black hole (SMBH) mass is estimated to be MBH ≈ 5 × 10 7 M after applying the bolometric correction of 4.4 (Willott et al 2010) to the observed UV luminosity. Non-thermal emission is evident from the high ionisation metal line N V as well as from the tentative 2.6 − 2.9σ detection of X-ray emission from 78 ks Chandra observation (Gallerani et al 2017).…”
Section: A Faint Agn and Broad Lyα Transmission Spikes At Z∼57mentioning
confidence: 77%
“…Archival data from the Spitzer and Chandra Space Telescopes provides additional information on the stellar mass and AGN activity of selected sources in the QSO field (e.g. Jiang et al 2006;Gallerani et al 2017).…”
Section: Observationsmentioning
confidence: 99%
“…Although this argument is still debated and might not be applied to all the obscured systems, there are some observational evidence confirming the presence of galaxy-scale absorbers in obscured QSOs (see e.g. Lanzuisi et al 2017 and references therein; Gallerani et al 2017;Gilli et al , 2014Rosario et al 2018;Symeonidis 2017). This is suggested, for example, by the correlation between the nuclear column density (N H ) and the amount of gas traced by the CO on kpc-scales (e.g.…”
Section: Introductionmentioning
confidence: 99%